2017
DOI: 10.1002/2016jb013505
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Sandbox modeling of evolving thrust wedges with different preexisting topographic relief: Implications for the longmen Shan thrust belt, eastern Tibet” by C. Sun et al.

Abstract: Sun et al.'s (2016) sandbox modeling takes preexisting topographic relief into account for faulting activity at the compressional orogenic belt, which promotes better understanding of Longmenshan thrust belt's (LTB) orogenic process and faulting behavior. However, topographic relief in sandbox modeling is contradictory to central LTB's actual topographic relief, and as a result, both the comparison between sandbox modeling and actual tectonics and topography and the conclusion that Xiaoyudong Fault is a tear f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Compared with the HKSS, the higher topography in the LMSS causes stronger normal stresses on the BYF (Figure ), which increases the friction along this subsegment (given a uniform coefficient of internal friction in the central LTB; Dahlen et al, ). Since it is not favorable to accommodate the strains solely on the BYF, thrust slips are thus partitioned onto the JGF in the LMSS, resulting in the along‐strike variation of the long‐term activity and coseismic slip on the JGF (Lu et al, ; Tan, Xu, Lee, et al, ; Tan, Xu, & Lu, ). Therefore, the topographic variations in the hanging‐wall block of the BYF play a major role in producing the long‐term fault activity and coseismic slip differences between the LMSS and HKSS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the HKSS, the higher topography in the LMSS causes stronger normal stresses on the BYF (Figure ), which increases the friction along this subsegment (given a uniform coefficient of internal friction in the central LTB; Dahlen et al, ). Since it is not favorable to accommodate the strains solely on the BYF, thrust slips are thus partitioned onto the JGF in the LMSS, resulting in the along‐strike variation of the long‐term activity and coseismic slip on the JGF (Lu et al, ; Tan, Xu, Lee, et al, ; Tan, Xu, & Lu, ). Therefore, the topographic variations in the hanging‐wall block of the BYF play a major role in producing the long‐term fault activity and coseismic slip differences between the LMSS and HKSS.…”
Section: Discussionmentioning
confidence: 99%
“…The Xiaoyudong fault is an enigmatic secondary structure in the central LTB that marks the boundary between the two subsegments (Figure ; Chang et al, ; Y. Li et al, ; Liu‐Zeng et al, ; Sun et al, ; Tan et al, ; Tan, Xu & Lu, ). The 8‐km‐long fault generally strikes northwest and dips to the southwest, with local, short wavelength fluctuation on the surface trace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the comment, Tan et al . [] conducted topographic analysis in the central Longmen Shan and provided two along‐strike topographic profiles located in the hanging wall and footwall of Yinxiu‐Beichuan fault separately. They concluded that southwest block of the Xiaoyudong fault is higher than its northeast counterpart.…”
Section: Topographic Relief Of the Longmen Shan Thrust Belt And The Dmentioning
confidence: 99%
“…The superficial transfer zone could be estimated more than 20 km, corresponding to the 20 km wide aftershock zone of Wenchuan earthquake in the same position [ Chang et al ., ]. However, the strike‐slip deformation represented by such a transfer zone in the Longmen Shan thrust belt would be more overestimated at a smaller length scale, for example, the 50 km scale [ Tan et al ., ], while the Longmen Shan is dominated by compression, not strike‐slip deformation. It is also the foundation of our model design.…”
Section: Topographic Relief Of the Longmen Shan Thrust Belt And The Dmentioning
confidence: 99%